A Pilot Study of Narrative Art Therapy on Psychological Wellbeing of Cancer Patients - Ando, Michiyo; Kashiwada, Tomomi; Kosugi, Toshifumi (Advances in Social Sciences Research Journal, 2023)
The present study aimed to make a new Psychological approach for cancer patients and investigate possibility and utility of it as a pilot study. We made a Narrative Art Therapy, which is an approach integrated narrative therapy with art therapy. They participated the Narrative Art Therapy in which they made arts and narrated their lives including illness. They completed the S-WHO-5-J to measure mental health, the Subject Happiness Scale, and the Self-Compassion Scale pre and post the therapy. Eight cancer patients under chemotherapy participated with the study and six completed. A completion rate was 75%. The S-WHO-5-J score increased from 8.5 to 9.5. The Subjective Happiness score increased from 4.94 to 5.50. Moreover, the Self-Compassion score increased from 41.7 to 48.7. These results suggest that Narrative Art Therapy has possibility to conduct for cancer patients and utility on mental health, subjective happiness, and self-compassion of them.